Exploring the Implications of the Stoichiometric Modulation of Planktonic Predation - Aditee Mitra (Aquatic Microbial Ecology and Biogeochemistry: A Dual Perspective, 2016)
Ecology involves the transfer of elements between organisms and the environment. Inevitably, and as exemplified in ‘stoichiometric ecology’, imbalances in the transfer pathways have potential to disturb trophic dynamics. It is also clear, though, that those disturbances are not simply (linearly, so to speak) related to imbalances in elemental stoichiometry (e.g., C:N:P). Rather trophic interactions, such as predation, appear extremely sensitive to minor changes in biochemical stoichiometry. This sensitive link between biochemical stoichiometry, subtle changes in composition affecting food quality between prey and predator, is termed stoichiometric modulation of predation (SMP). Here, we discuss the impact of SMP across various facets of plankton trophic dynamics. These include comparisons between SMP being involved in promotion of harmful algal blooms versus the same interactions being exploited to contain damage to commercial crops of microalgae from zooplanktonic pests. Also, considered are the implications of climate change events—warming, ocean acidification and eutrophication—upon SMP, for the formation or dissipation of ecosystem disruptive blooms. Then there is the issue of how and when primary producers exploit what we see as SMP as a means to limit predation on their own kind, thus shifting grazing pressure onto competitor primary producers. Finally, we consider mixotrophy and SMP; how within a single celled organism the heterotrophic base may be operated in a non-stressed state while control of the phototrophic component may have evolved to allow sufficient stress to promote the synthesis of noxious secondary metabolites that deter grazers. Understanding and modelling the implications of biochemical stoichiometric ecology appears to offer a rich vein for future plankton research.